2001
DOI: 10.2337/diabetes.50.12.2874
|View full text |Cite
|
Sign up to set email alerts
|

Further Mapping of the Idd5.1 Locus for Autoimmune Diabetes in NOD Mice

Abstract: The Idd5 locus for autoimmune diabetes in nonobese diabetic (NOD) mice has been mapped to the proximal half of chromosome 1 and appears to include two loci, Idd5.1 and Idd5.2, Idd5.1 being a candidate homolog of the human IDDM12 locus. Using new recombinant congenic lines, we have reduced the Idd5.1 interval to 5 cM at most, between D1Mit279 and D1Mit19 (not included). This interval now excludes the Casp8 and Cflar (Flip) candidate genes. It still retains Cd28 and Ctla4 and also includes Icos (inducible costim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…In addition, the 129-derived interval encompassing the IL-1R knockout has been localized, at present, between D1Mit167 and D1Mit322 (not included). This interval is ϳ6.9 cM proximal to the previously described boundary for Idd5.1 and, to date, has not been implicated in disease susceptibility or resistance (32,33).…”
Section: Resultsmentioning
confidence: 66%
“…In addition, the 129-derived interval encompassing the IL-1R knockout has been localized, at present, between D1Mit167 and D1Mit322 (not included). This interval is ϳ6.9 cM proximal to the previously described boundary for Idd5.1 and, to date, has not been implicated in disease susceptibility or resistance (32,33).…”
Section: Resultsmentioning
confidence: 66%
“…1 to a region previously defined as Idd5.1 using NOD stocks bearing various truncations of B10-or B6-derived congenic segment. 29,30 However, within the peak linkage interval assigned by the software, all NOR markers typed proved to share allelic identity with NOD including a Ctla4 SNP that is likely to be the actual Idd5.1 susceptibility variant. 15 Thus, it is possible that the computer assigned peak linkage to the Idd5.1 region is an artifact, and in reality is due to contributions from two flanking loci each containing at least one diabetes resistance gene.…”
Section: Discussionmentioning
confidence: 97%
“…However, the strongest evidence for a direct effect of allelic variation of CTLA4 on type 1 diabetes susceptibility is provided by studies in the non-obese diabetic (NOD) mouse [14,[29][30][31]. Genetic analysis of the NOD mouse model of type 1 diabetes has shown that the region of mouse chromosome 1 containing Ctla4 and the insulin dependent diabetes susceptibility 5a (Idd5a, previously known as Idd5.1) locus has a significant effect on disease susceptibility [14,[29][30][31]. The causal variant has been mapped to a SNP in exon 2 of Ctla4, for which the NOD allele reduces the splicing and production of an alternative mRNA isoform of CTLA4, the ligand-independent form (liCTLA4) [14].…”
Section: Discussionmentioning
confidence: 99%